2017
DOI: 10.1016/j.gene.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in two large pedigrees highlight the role of ZNF711 in X-linked intellectual disability

Abstract: Intellectual disability (ID) affects approximately 1-2% of the general population and is characterized by impaired cognitive abilities. ID is both clinically as well as genetically heterogeneous, up to 2000 genes are estimated to be involved in the emergence of the disease with various clinical presentations. For many genes, only a few patients have been reported and causality of some genes has been questioned upon the discovery of apparent loss-offunction mutations in healthy controls. Description of addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…For the SNV in ZNF711, there was felt to be insufficient evidence in support of pathogenicity at the time of the initial review. The identification of additional cases has now bolstered the argument for causality [24].…”
Section: Resultsmentioning
confidence: 98%
“…For the SNV in ZNF711, there was felt to be insufficient evidence in support of pathogenicity at the time of the initial review. The identification of additional cases has now bolstered the argument for causality [24].…”
Section: Resultsmentioning
confidence: 98%
“…Clinical reports of sporadic cases also support this pathogenetic connection [11]. Recently in 11 male patients from two new found MRX97 families, Van der Welf et al [12] identified a frameshift deletion and a missence mutation in ZNF711 which both predict the deleterious effect and cause the disease. By expression analysis of cell culture, they also showed that these mutations induced differential expression of genes known to be expressed in the brain compared to controls, which adds evidence to ZNF711 as a transcription factor.…”
Section: Discussionmentioning
confidence: 96%
“…There are twelve genes located within this duplication, half of which have been linked to a clinical phenotype. Although the exact function of the zinc finger protein ZNF711 is unknown, variants in this gene have been described as associated with cognitive disability [38]. Similarly, mutations in BRWD3 , which may have a chromatin-binding function, have been associated with cognitive disabilities [39,40], and the ribosomal S6-kinase, RPS6KA6 , is commonly deleted in patients with X-linked mental retardation [41].…”
Section: Discussionmentioning
confidence: 99%